Incentives, choice and accountability in the provision of public services - Timothy Besley; Maitreesh Ghatak (Institute for Fiscal Studies (IFS), 2003)
This paper discusses a theoretical framework to study the issues of competition and incentives without relying on the standard profit-oriented “market” model in the context of the debates about public service reform in the UK. It uses the idea that the production of public services coheres around a mission, and discusses how decentralized service provision can raise productivity by matching motivated workers to their preferred missions. Our focus on competition and incentives cuts across traditional debates about public versus private ownership and allows for the possibility of involving private non-profits. We also address concerns about the consequences of allowing more flexibility in mission design and competition on inequality.
Keywords: 330; Öffentliche Dienstleistung; Wettbewerb; Ökonomischer Anreiz; Theorie